High‐Pressure Synthesis of Manganese Oxyhydride with Partial Anion Order. (29th June 2016) - Tassel, Cedric; Goto, Yoshinori; Watabe, Daichi; Tang, Ya; Lu, Honcheng; Kuno, Yoshinori; Takeiri, Fumitaka; Yamamoto, Takafumi; Brown, Craig M.; Hester, James; Kobayashi, Yoji; Kageyama, Hiroshi
Abstract: The high‐pressure synthesis of a manganese oxyhydride LaSrMnO3.3 H0.7 is reported. Neutron and X‐ray Rietveld analyses showed that this compound adopts the K2 NiF4 structure with hydride ions positioned exclusively at the equatorial site. This result makes a striking contrast to topochemical reductions of LaSrMnO4 that result in only oxygen‐deficient phases down to LaSrMnO3.5 . This suggests that high H2 pressure plays a key role in stabilizing the oxyhydride phase, offering an opportunity to synthesize other transition‐metal oxyhydrides. Magnetic susceptibility revealed a spin‐glass transition at 24 K that is due to competing ferromagnetic (Mn 2+ –Mn 3+ ) and antiferromagnetic (Mn 2+ –Mn 2, Mn 3+ –Mn 3+ ) interactions.